Pengembangan Usaha Fashion Thrift dalam Mendukung Sustainable Fashion di Kota Maumere: Pendekatan Analisis SWOT - Theresia Winarti; Maria Natalia; Christina Natalia; Ermelinda Getrilda Da Cunha; Alberth Alfredo Gajon (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the development strategy of the Jeanete business, located in Maumere City, Jl. Kesehatan No. 3, Lorong Masuk SDK Yos Sudarso, through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis approach. The research employed a descriptive qualitative method using field observations, in-depth interviews with business owners, and documentation as data collection techniques. SWOT analysis was applied to identify internal and external factors influencing the growth of fashion thrift businesses. The findings indicate that the business strengths include affordable product prices, good-quality secondhand clothing, and increasing consumer interest in thrift fashion products. The identified weaknesses consist of limited business capital, unstable product supply, and inadequate utilization of digital marketing. Opportunities arise from the growing public awareness of sustainable lifestyles, rapid digital technology development, and the increasing popularity of thrift fashion among younger generations. Meanwhile, threats include intensifying competition, rapidly changing fashion trends, and fluctuations in product supply costs. Based on the SWOT matrix analysis, the recommended strategies involve strengthening digital marketing activities, improving customer service quality, diversifying products, expanding supplier networks, and implementing sustainability-oriented business practices. The study concludes that fashion thrift businesses have significant potential to grow while contributing to textile waste reduction and promoting sustainable fashion practices in Maumere City.